Assessing learning environments: a case study of engineering students’ satisfaction at diploma level - Muda, Mohd Fakri; Alias, Rohaya; Zainudin, Mohd Razmi; Mohd Hashim, Mohd Hisbany; Ab Rahman, Marzuki; Mokhtar, Hamizah; Ab Latif, Amminudin (GADING Journal for the Social Sciences, 2025)
The recent trend of diminishing interest in higher education among the youth presents a critical challenge, affecting the future workforce and the nation's ability to innovate and remain competitive. This study examines the factors influencing student engagement and satisfaction in an engineering program at a public university. The study focuses on the relationship between students’ academic backgrounds and their perception of the difficulty of university subjects. A comprehensive survey of 39 new engineering students was undertaken in period of six weeks into lectures. The findings indicate that subjects with complex of conceptual understanding, problem-solving requirements, and mathematical applications, like Physics, were considered the most challenging, regardless of students’ prior academic achievements. The survey additionally reveals a sense of obligation, especially among female students, rather than a genuine interest in the program. Analysis suggests that prior performance in subjects like Additional Mathematics significantly impacts’ students’ experiences in their current engineering courses. The study concludes with several recommendations to improve student retention and sustain interest in higher education pursuits. These include refining the curriculum, enhancing English language assistance, and implementing specialised initiatives for female students. These recommendations provide actionable insights for educational institutions to enhance student experiences and counter the downward trend in higher education enrolment.